Sosialisasi dan Simulasi Mitigasi Bencana Alam Pada Siswa SMP Kemala Bhayangkari 9 Waru Dalam Menghadapi Bencana Alam - J.A. Jelita Srikandi Pertiwi; Zawawi Zawawi (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
Geologically, Indonesia is located along the Ring of Fire, a volcanic line that surrounds the Pacific Ocean, making Indonesia a vulnerable country and has the potential to experience natural disasters. This is not proportional to the ability and readiness of the community in dealing with natural disasters. This community service socialization and disaster mitigation simulation was carried out to Kemala Bhayangkari 9 Waru Junior High School Students which aims to provide education to be alert when facing natural disasters, especially earthquakes. This socialization and simulation is very effective as seen from the students practicing the simulations that we demonstrate, so it can also be assessed that students really understand and are ready if there is a natural disaster